South Africa's labour framework: have the realities of employment been accommodated for? - Vlieghe, Stephen (Department of Commercial Law, 2026)
Labour Law is a dynamic field that is the subject of constant change. In the individual labour law context, this change is attributable to a multitude of forces that continuously shape the nature of employment relations, leaving Labour Law with the task of updating itself accordingly. This paper focuses on two of these forces, namely, casualisation and externalisation. The aim has essentially been to ascertain whether the development of Labour Law in South Africa has been able to keep up with the changing nature of employment. In order to gauge whether it has, reference has been made to what the purpose of Labour Law is. The fact that the vast majority of individuals will engage in productive work during some period in their lives makes consideration of this topic an absolute necessity. In formulating a conclusion, this paper is intended to reveal both a ray of sunshine and a dark cloud that simultaneously loom over the boundaries that currently shape labour law.